Influence of Parental Guidance on Learning Outcomes among Preschoolers in Masaba South Sub-County, Kisii County - , Lydiah N. Onkoba; Simon Nyakwara (IJRDO- Journal of Educational Research, 2020)
Parent involvement is often considered a pathway through which schools enhance the achievement of underperforming children. However, past research on parent involvement and children’s academic skills has yielded mixed results. Therefore, the main objective of the study was to examine the influence of parental guidance on learning outcomes among preschoolers in Masaba South Sub County, Kisii County. The study was guided by the Cultural capital theory and supported Epstein’s Theory of Comprehensive School Reform Model. The study used the mixed methods approach together with the triangulation design targeting the parents of the preschoolers, the pre-primary school teachers the school managers and the Sub County Education Officers in charge of pre-primary education. A sample size of 120 responents was obtained through purposive sampling method was to be used for the study. Data was collected through questionnaires and was analyzed using both descriptive and inferential statistical methods.Piloting of the instruments will be conducted on 10% of the sample size, all from Kisii CentralSub County, Kisii County. Piloting helped to establish reliability, credibility and dependability of the instruments. Reliability index r = 0.64 was obtained using Cronbach Alpha to check internal consistency. Credibility was ensured through involving different analysts while dependability was manifested through comprehensive reporting and independent interview to respondents. Data analysis involved qualitative data being analyzed in themes while quantitative data through descriptive statistics and inferential statistics with the use of Statistical Packages for Social Sciences (SPSS 23) and presented using tables and charts. The findings of this study are meant to enlighten the stakeholders in preschool on the need for parental guidance as an intervention meant to address performance of preschoolers. This would be instrumental in shaping practice and policy decisions as well as future research directions.